Strategi Pengembangan Bisnis Pemotongan Sapi - Aisa Rurkinantia; Rina Oktaviani; Bunasor Sanim (Jurnal Aplikasi Bisnis dan Manajemen (JABM), 2017)
The purpose of this study are 1) to identify the internal and external factors that influence development strategy of beef cattle business, 2) to make the alternative strategy, and 3) to make priority of strategy for development of beef cattle business in of PD. Kampung 99 Pepohonan. This study uses IFE and EFE Matrix, analysis SWOT matrix and QSPM. Respondens for this study are 10 persons that are 5 internal respondes, and 5 external respondes. To Determine of priority strategy,this study uses IFE and EFE matrix, SWOT matrix and QSPM analysis. The main priority strategy development strategy that can be implemented is increase cattle quality with serve the optimum feed for the cow with get enough on recovery time. The next priority strategy is to submitted decrease loan interest in working capital of the bank, multiplied of line distribution between home beef cattle and feedlot and revitalitation between home beef cattle as the place of meat proceccing to filled the market needed.Keywords: beef cattle, PD. Kampung 99 Pepohonan, EFE,SWOT, QSPMAbsrak: Tujuan dari penelitian ini adalah 1) untuk mengidentifikasi factor-faktor internal dan eksternal, 2) menentukan alternatif strategi, dan 3) strategi prioritas untuk mengembangkan usaha pemotongan sapi di PD. Kampung 99 Pepohonan. Penilitian ini menggunakan Matriks IFE dan EFE, Matrik SWOT dan QSPM. Jumlah responden internal sebanyak 5 orang dan eksternal sebanyak 5 orang. Hasil penelitian menunjukkan bahwa meningkatkan kualitas potongan daging sapi dengan menyediakan pakan yang optimal serta masa recovery yang cukup sebelum dilaksanakannya pemotongan sapi. Untuk strategi prioritas selanjutnya adalah dengan mengajukan penurunan bunga pinjaman modal kerja dari bank, memperbanyak saluran distribusi antar rumah potong hewan (RPH) dan Feedloot dan revitalisasi RPH sebagai tempat meat proceccing untuk memenuhi kebutuhan pasar.Kata kunci: pemotongan sapi, PD. Kampung 99 Pepohonan, EFE ,SWOT, QSPM